Penerapan Artificial Inteligence (AI) pada Robot Asuhan Keperawatan NAR dalam Peningkatan Efektivitas Kinerja Kerja di Rumah Sakit - Richie Marlon; Henly h; Joyce j; Shella s; Juven Gautama; Rido Renando; Welliam Ali (Journal of Information System and Technology (JOINT), 2020)
At the beginning of 2020, the symptoms of the Corona Virus or Covid-19 have hit almost all countries in the world. The effects of these symptoms can cause various symptoms such as cough, flu / cold, fever, and other symptoms. As we know, this symptom can be spread through direct contact with sufferers and also through droplets released when coughing or sneezing. One way to prevent these symptoms is to lockdown or self-quarantine and follow established health protocols. There have been many hospitals that have been designated for patients with Covid-19 symptoms, and the Government has also built a special hospital aimed at patients infected with Covid-19 symptoms on Galang Island, Batam, Riau Islands. The doctors and nurses at the hospital were tired and didn't get enough rest due to caring for Covid-19 patients. In medicine, Artificial Intelligent (AI) plays a role in helping medical robots in the world of nursing to analyze the impact of robot nurse technology for nursing services. Robot nurse or robot nurse is currently developing rapidly due to a virus that can spread very quickly, namely, COVID-19. This robot has also been designed to be able to interact with humans. The development of robot nurses is influenced by several factors including the increasing spread of infectious diseases, an increase in the elderly population, the lack of time for nurses to attend to patients and the limited resources of nurses. The Artificial Intelligent (AI) system shows us the beginning of using nursing robots and the impact caused by the use of these robots.